Local tumor control and treatment related toxicity after plaque brachytherapy for uveal melanoma: A systematic review and a data pooled analysis. (January 2022) - Buonanno, Francesca; Conson, Manuel; de Almeida Ribeiro, Cintia; Oliviero, Caterina; Itta, Francesca; Liuzzi, Raffaele; Pacelli, Roberto; Cella, Laura; Clemente, Stefania
Highlights: EPB is the most frequently used eye-sparing treatment option for small to medium sized UMs. We present a systematic review of the literature from the last sixteen years on EPB treatment of UM. Ru-106 EPB provided high local control outcomes minimizing radiation induced complications. TCP and NTCP on pooled clinical outcomes was performed for 5-year LTC, cataract and optic neuropathy. Abstract: Uveal melanoma (UM) represents the most common primary intraocular tumor, and nowadays eye plaque brachytherapy (EPB) is the most frequently used visual acuity preservation treatment option for small to medium sized UMs. The excellent local tumor control (LTC) rate achieved by EPB may be associated with severe complications and adverse events. Several dosimetric and clinical risk factors for the development of EPB-related ocular morbidity can be identified. However, morbidity predictive models specifically developed for EPB are still scarce. PRISMA methodology was used for the present systematic review of articles indexed in PubMed in the last sixteen years on EPB treatment of UM which aims at determining the major factors affecting local tumor control and ocular morbidities. To our knowledge, for the first time in EPB field, local tumor control probability (TCP) and normal tissue complication probability (NTCP) modelling on pooled clinical outcomes were performed. The analyzed literature (103 studies including 21, 263 UM patients) pointed out that Ru-106 EPB provided high local control outcomes while minimizing radiation induced complications. The use of treatment planning systems (TPS) was the most influencing factor for EPB outcomes such as metastasis occurrence, enucleation, and disease specific survival, irrespective of radioactive implant type. TCP and NTCP parameters were successfully extracted for 5-year LTC, cataract and optic neuropathy. In future studies, more consistent recordings of ocular morbidities along with accurate estimation of doses through routine use of TPS are needed to expand and improve the robustness of toxicity risk prediction in EPB.